LEGAL ASPECT OF ONLINE ARBITRATION IN EUROPEAN UNION AND CHINA - Manja Indah Sari (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2019)
Indonesia is highly regarded as a country with the biggest e-commerce market in South-East Asia. This creates an urgency for the Indonesian government to offer an efficient and effective dispute resolution mechanism to settle dispute arising from e-commerce transaction. Online arbitration as an arbitration conducted online through means of internet and technology may provide solution to the disputes arising from e-commerce transactions. Thus, this article sets out the legal aspect of online arbitration in European Union and China as countries with the most developed online arbitration and largest market of e-commerce. The author will use normative research through comparative, statue approach and will be based on the regulations from primary and secondary resources. This article compares six aspects of online arbitration in European Union and China, covering the arbiter, role of government, scope, procedure, enforcement, and factors affecting enforcement. The comparison may give further recommendation on the prospective of online arbitration in Indonesia.